Zánět a ateroskleróza - Poledne, Rudolf; Lesná, Ivana Králová (Vnitrni lekarstvi, 2019)
Although current treatment of hypertension and hypercholesterolemia is most effective, cardiovascular mortality still remains at 50 % in industrialized countries. This could be explained by the rather high contribution of the inflammatory process to atherogenesis development. Use of high-sensitivity C-reactive protein (hsCRP) determination in several large epidemiological studies has made it possible to document increased risk of myocardial infarction in individuals with slightly increased hsCRP concentrations, which could thus serve as a discriminatory factor in cardiovascular disease risk assessment. However, the situation is not that simple since hsCRP concentrations correlate significantly with BMI, age and smoking as major cardiovascular risk factors. Increased proportion of pro-inflammatory macrophages in visceral adipose tissue has also been shown to rise with BMI, age (differently in men and women) and non-HDL-cholesterol levels. It has been suggested that the pro-inflammatory status induced by a higher proportion of pro-inflammatory macrophages in visceral adipose tissue acts synergistically in atherogenesis development. Key words: atherosclerosis - cardiovascular disease - inflammation.
Keywords: C-Reactive Protein; Inflammation; mediátory zánětu; C-reaktivní protein; zánět; mužské pohlaví; ateroskleróza; Inflammation Mediators; Atherosclerosis; Cardiovascular Diseases; ženské pohlaví; Humans; biologické markery; rizikové faktory; atherosclerosis - cardiovascular disease - inflammation; Biomarkers; Female; Risk Factors; kardiovaskulární nemoci; lidé; Male